2018
DOI: 10.1002/mbo3.696
|View full text |Cite
|
Sign up to set email alerts
|

The invasive cell coat at the microsporidian Trachipleistophora hominis–host cell interface contains secreted hexokinases

Abstract: Microsporidia are obligate intracellular parasites causing significant disease in humans and economically important animals. In parallel to their extreme genetic reduction, Microsporidia have evolved novel mechanisms for exploiting host metabolism. A number of microsporidians confer secretion of otherwise cytosolic proteins by coding for signal peptides that direct entry into the endoplasmic reticulum. The human pathogen Trachipleistophora hominis encodes for four hexokinases, three of which have signal peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…The most extensively studied microsporidia protein that directly interacts with hosts is hexokinase. Microsporidia hexokinases have gained a signal peptide and were experimentally shown to be secreted in several species [19,[44][45][46]. This enzyme potentially increases host metabolism to provide nutrients for the developing parasites, and consistent with this idea, knockdown of the enzyme reduces microsporidia proliferation [44].…”
Section: How Have Microsporidia Adapted To Their Hosts?mentioning
confidence: 85%
“…The most extensively studied microsporidia protein that directly interacts with hosts is hexokinase. Microsporidia hexokinases have gained a signal peptide and were experimentally shown to be secreted in several species [19,[44][45][46]. This enzyme potentially increases host metabolism to provide nutrients for the developing parasites, and consistent with this idea, knockdown of the enzyme reduces microsporidia proliferation [44].…”
Section: How Have Microsporidia Adapted To Their Hosts?mentioning
confidence: 85%
“…Manuscript to be reviewed localization inside host cells. The location of NbHK during the proliferation stage of N. bombycis infection implied it may play a role in regulating and controlling the host's energy metabolism (Ferguson & Lucocq 2018).. HK, with or without its signal peptide, and fused with DsRed was expressed in BmN cells, which showed a similar subcellular localization. The localization of eukaryotic expressed rHK revealed that the signal peptide could not lead the rHK to be secreted or to enter into nuclei of healthy BmN or Sf9-III.…”
Section: Discussionmentioning
confidence: 97%
“…The high transcription of NbHK and its importance function implied the glycolysis also play a key role during its intracellular stages, even microsporidia could steal ATP from host.HK is a control valve of glycolysis. The secretory HK of microsporidia turn up the valve of glycolysis and the tricarboxylic acid cycle, which is a clever strategy to steal energy from the host (Ferguson & Lucocq 2018).…”
Section: Discussionmentioning
confidence: 99%
“…NbHK was predicted to be a secretory protein with a signal peptide, suggesting its potential localization inside host cells. The location of NbHK during the proliferation stage of N. bombycis infection implied it may play a role in regulating and controlling the host’s energy metabolism ( Ferguson & Lucocq, 2018 ). HK, with or without its signal peptide, and fused with DsRed was expressed in BmN cells, which showed a similar subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…The P. locustae HK was predicted to contain a signal peptide, and the indirect immunofluorescent assay (IFA) showed a nuclear localization in the host ( Senderskiy et al, 2014 ; Timofeev et al, 2017 ). Then, special secreting hexokinase function which work as a regulator to increase ATP generation to parasite surface, was explored in Trachipleistophora hominis ( Ferguson & Lucocq, 2018 ).…”
Section: Introductionmentioning
confidence: 99%